THE INFLUENCE ON THE EFFECTIVENESS OF ROLLING EMPLOYEES WORK IN MANADO STATE ISLAMIC INSTITUTE (IAIN) - Ridwan Tabe (IAIN Manado, 2017)
Abstract Influence on the effectiveness of Rolling employees work in Manado State Islamic Institute. This study was conducted to address the effect of rolling on the effectiveness of employees working in Manado IAIN environment, thus the goal of this research is to know how to influence employees rolling on the readiness of the effectiveness of work in the neighborhood IAIN Manado. This research is a quantitative research for the study use a lot of numbers, ranging from data collection to the interpretation of the data. Besides this empirically is an ex post-facto research because the data obtained is data results from the events that have taken place, while the technique of data collection using questionnaires which is conducted by researchers to obtain accurate information. Data analysis technique used is simple regression techniques. The results of this study indicate that Rolling employees has positive and significant impact to the effectiveness of work in IAIN Manado as indicated by the results of the analysis of the correlation coefficient (rx,y) of 0. 826 and the value coefficient determinant (r2x,y) of 0.682 and thitung7.319> ttabel 2.060 or p. (0.000< 0.05 at significant level of 5 per cent, it means rolling variable Rolling employees effecting the effectiveness of work by 68.20%. Keywords: rolling employees, effectiveness of work